Electromyographic study of the trapezius (upper portion) and levator scapulae muscles in some movements of the shoulders - Longo Bull, M.; Vitti, M.; De Freitas, V. (My University, 1985)
The trapezius (upper portion) and levator scapulae mm. were analyzed in 30 adult volunteers of both sexes with a 2 channel TECA TE4 electromyograph and single coaxial needle electrodes. It was noticed that in elevation and lowering of the shoulders both muscles act synergically, and during the lowering, they act to control the return of the shoulders to the initial position. During retraction and protraction of the shoulders these muscles are inactive. In these movements no significant difference was noticed in the activity of these muscles in relation to sex.